First record of the starfish Goniaster tesselatus at Madeira Island - Wirtz, Peter (2022)
Numerous new records of marine species have been made at Madeira Island in recent years (e. g. Ramalhosa et al. 2014, 2017, Wirtz 2020 a, Wirtz & Araujo 2021). Some of these species appear to have extended their range northwards (e. g. Wirtz & Berenger 2017, Schäfer et al. 2019, Wirtz 2021), possibly due to global warming (Siemer et al. 2021). Eleven shallow-water starfish species are known from Madeira Island (Wirtz 2020 b). We report here on one more species previous, unrecorded for Madeiran waters.